Motor Coordination and Strategic Cooperation in Joint Action. (May 2022) - Bars, Solène Le; Bourgeois-Gironde, Sacha; Wyart, Valentin; Sari, Izel; Pacherie, Elisabeth; Chambon, Valérian
Naturalistic joint action between two agents typically requires both motor coordination and strategic cooperation. However, these two fundamental processes have systematically been studied independently. We presented 50 dyads of adult participants with a novel collaborative task that combined different levels of motor noise with different levels of strategic noise, to determine whether the sense of agency (the experience of control over an action) reflects the interplay between these low-level (motor) and high-level (strategic) dimensions. We also examined how dominance in motor control could influence prosocial behaviors. We found that self-agency was particularly dependent on motor cues, whereas joint agency was particularly dependent on strategic cues. We suggest that the prime importance of strategic cues to joint agency reflects the co-representation of coagents' interests during the task. Furthermore, we observed a reduction in prosocial strategies in agents who exerted dominant motor control over joint action, showing that the strategic dimension of human interactions is also susceptible to the influence of low-level motor characteristics.